UNRAVELING THE IMPACT OF NETWORK COMPOSITION ON EDUCATIONAL OUTCOMES: A STUDY OF MEXICAN-ORIGIN YOUTH - Hoxby, HCaroline (Journal of Current Research and Review (JCRR), 2022)
The Hispanic-origin population in the United States has made significant strides in educational attainment in recent years. However, Mexican-origin youth continue to face challenges in completing their education, with lower rates of college enrollment and degree attainment compared to other racial and ethnic groups. This study examines the role of peer and friendship networks in contributing to educational disparities between Mexican-origin and non-Mexican students. It explores the influence of the socioeconomic backgrounds of peers and friends on the educational outcomes of Mexican-origin youth. Drawing on data from the National Longitudinal Study of Adolescent to Adult Health, the study examines the composition of social networks and the influence of network resources on educational achievement. The data include information on students' peers' socioeconomic backgrounds as well as friendship nominations, enabling the construction of social networks. By separately analyzing the role of peers and friends, the study investigates the unique effects of these relationships on students' educational progress. The findings reveal significant differences in the socioeconomic backgrounds of friends and peers between Mexican-origin and non-Mexican students. While the formal schooling of network alters positively affects college transition for non-Hispanic white students, there is little evidence to suggest that socioeconomic resources in peer or friend networks contribute meaningfully to the educational outcomes of Mexican-origin students. This suggests that addressing structural disadvantages beyond peer and friend networks may be more effective in supporting educational advancement among Mexican-origin youth. The study highlights the need to consider resources beyond formal schooling that are most relevant to the educational progress of Mexican-origin students. It also underscores the importance of understanding the broader context of structural constraints faced by Mexican-origin youth